Endoscopically assisted computer-guided repair of internal orbital floor fractures: an updated protocol for minimally invasive management. Issue 12 (December 2019) - Tel, Alessandro; Sembronio, Salvatore; Costa, Fabio; Stenico, Alessandro Scipio; Bagatto, Daniele; D'Agostini, Serena; Robiony, Massimo
Abstract: Background: Performing accurate anatomical reconstruction is a challenging task in the treatment of internal orbital floor fractures. Compared with traditional transcutaneous incisions, endoscopic transmaxillary approaches have the advantage of avoiding complications related to external scars, and provide direct access to the orbital floor. Autogenous bone provides the ideal material for defect reconstruction, but determination of the correct size and shape of the graft is crucial for a stable support. This study introduces a new protocol for the treatment of internal orbital floor fractures that combines endoscopy, virtual reality, and 3D printing. The authors also investigated the impact of computer-aided surgery (CAS) on the overall accuracy of reconstruction in aiming to achieve the triple objective of restoring anatomy, volume, and function. Materials and methods: Fourteen patients with orbital floor fractures were recruited for this study. High-resolution CT scans provided appropriate imaging for detailed orbital floor defect visualization. A virtual reconstruction of the orbital floor defect was developed and a 3D printed template was fabricated to provide intraoperative guidance in the graft harvesting phase, according to the orbital defect. Virtual analyses were conducted to evaluate the accuracy of reconstruction both in terms of graft size and graft orientation. Results: Postoperative CT scans showed that in all cases orbital floor reconstruction was successfully performed, resulting in restoration of the correct globe position. No intraoperative complications occurred. Correspondence of graft size was evaluated using color-coded maps and RMSE, while comparison of angular measurements allowed the authors to relate simulated and actual reconstruction. Conclusions: Orbital floor reconstruction performed via transmaxillary endoscopy is a safe technique, which allows for detailed visualization of the fracture rim, avoids external scars, and permits an easier reduction of the prolapsed orbital content into the overlying orbital cavity. Virtual planning plays an important role in defining the appropriate geometry of the bone graft and establishing the optimal reconstruction strategy. Our preliminary results indicate that virtual planning and 3D printing should become part of an integrated protocol for the endoscopic treatment of orbital floor fractures.